Perkembangan Bahasa dan Sastra Masa Bani Abbasiyah II - Azhari, Arina Fitriya (Maliki Interdisciplinary Journal, 2025)
The Abbasid period, especially the second phase (232–334 AH / 847–945 AD), was an important period in the development of Arabic language and literature. Although Abbasid political power began to weaken, intellectual, cultural, and social dynamics encouraged innovation in literature. Factors such as the importance of preserving the purity of the Arabic language, religious fervor, the emergence of various ethnic groups in government, and the development of science had a major influence on changes in language and literary style. During this period, literary themes and genres became increasingly diverse, especially in the form of poetry and prose. Poetry was no longer confined to classical traditions but underwent renewal with the emergence of genres such as siyasiyah, madh, hija’, ghazal, al-lahwu wa al-mujun, thardiyyat, and zuhdiyyat. Meanwhile, prose progressed through allegorical, philosophical, and moralistic works. These developments show that Abbasid II literature was not only an aesthetic medium, but also a means of social, political, intellectual, and spiritual expression. Thus, the Abbasid II period can be considered an important period for the formation of a more dynamic and culturally rich Arab literary identity.